Bridging the notch: quantification of the end diastolic notch to better predict fetal growth restriction - Yu, Sheila; Nair, Ananya Gopika; Huang, Tianhua; Melamed, Nir; Mei Dan, Elad; Aviram, Amir (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose We aimed to evaluate several quantitative methods to describe the diastolic notch (DN) and compare their performance in the prediction of fetal growth restriction.Materials and Methods Patients who underwent a placental scan at 16–26 weeks of gestation and delivered between Jan 2016 and Dec 2020 were included. The uterine artery pulsatility index was measured for all of the patients. In patients with a DN, it was quantified using the notch index and notch depth index. Odds ratios for small for gestational age neonates (defined as birth weight <10th and <5th percentile) were calculated. Predictive values of uterine artery pulsatility, notch, and notch depth index for fetal growth restriction were calculated.Results Overall, 514 patients were included, with 69 (13.4%) of them delivering a small for gestational age neonate (birth weight<10th percentile). Of these, 20 (20.9%) had a mean uterine artery pulsatility index >95th percentile, 13 (18.8%) had a unilateral notch, and 11 (15.9%) had a bilateral notch. 16 patients (23.2%) had both a high uterine artery pulsatility index (>95th percentile) and a diastolic notch. Comparison of the performance between uterine artery pulsatility, notch, and notch depth index using receiver operating characteristic curves to predict fetal growth restriction <10th percentile found area under the curve values of 0.659, 0.679, and 0.704, respectively, with overlapping confidence intervals.Conclusion Quantifying the diastolic notch at 16–26 weeks of gestation did not provide any added benefit in terms of prediction of neonatal birth weight below the 10th or 5th percentile for gestational age, compared with uterine artery pulsatility index.
Keywords: pulsatility index; uterine artery; fetal growth restriction; end diastolic notch